The Investigation of Literature as a Learning Media in Primary School - Dyani, Adhelya Putri; Halizah, Istiqomah Nur; Millah, Rifdatul; Rohmana, Wahyu Indah Mala (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This research explores the didactic function of literature with a focus on its role as a learning medium in English language education at MI Sunan Kalijaga Malang, East Java. Using a descriptive qualitative method, the study utilized observation, documentation and interviews conducted with the grade 4 English teacher and 36 students. The literature investigation in this study is the use of reading books as the main learning media and the distinctive features of the curriculum applied at various grade levels. The difficulties faced by English teachers, who are aware of this problem, took the initiative to include their own curriculum reading materials to ensure a more cohesive learning experience for students. The importance of customized and contextually relevant learning materials, taking into account the differences between the K-13 curriculum and the standalone curriculum in terms of its integration with students' daily lives.